2020
DOI: 10.1073/pnas.1916166117
|View full text |Cite
|
Sign up to set email alerts
|

Determining the correct stoichiometry of Kv2.1/Kv6.4 heterotetramers, functional in multiple stoichiometrical configurations

Abstract: The electrically silent (KvS) members of the voltage-gated potassium (Kv) subfamilies Kv5, Kv6, Kv8, and Kv9 selectively modulate Kv2 subunits by forming heterotetrameric Kv2/KvS channels. Based on the reported 3:1 stoichiometry of Kv2.1/Kv9.3 channels, we tested the hypothesis that Kv2.1/Kv6.4 channels express, in contrast to the assumed 3:1, in a 2:2 stoichiometry. We investigate the Kv2.1/Kv6.4 stoichiometry using single subunit counting and functional characterization of tetrameric concatemers. For selecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 57 publications
3
15
1
Order By: Relevance
“…In their Letter (1), Pisupati et al comment that they found a different Kv2.1:Kv6.4 stoichiometry (2) than we report in Möller et al (3). Our manuscript was still under review when their article was published.…”
mentioning
confidence: 60%
See 1 more Smart Citation
“…In their Letter (1), Pisupati et al comment that they found a different Kv2.1:Kv6.4 stoichiometry (2) than we report in Möller et al (3). Our manuscript was still under review when their article was published.…”
mentioning
confidence: 60%
“…Our manuscript was still under review when their article was published. Realizing that the results were inconsistent, we added an objective evaluation algorithm calculating relative probabilities for the different stoichiometry models (3).…”
mentioning
confidence: 99%
“…Gene expression studies show that KvS subunit family members have restricted regional and cellular expression patterns in mouse brain, which partially overlap with that of Kv2.1 and Kv2.2 (e.g., Allen Brain Atlas, Mousebrain.org) (Bocksteins, 2016). For example, Kv5.1 (KCNF1) mRNA is broadly expressed in cortex (Drewe et al, 1992) (Moller et al, 2020) or 3:1 (Kerschensteiner et al, 2005;Pisupati et al, 2018). In Kv5.1 IPs from brain, we find that the ratio of spectral counts for Kv2 to Kv5.1 subunits is ~3.5:1, and ~2.3:1 when normalized for either the number of observed unique peptides or expected tryptic peptides per subunit.…”
Section: Discussionmentioning
confidence: 99%
“…Rather, they obligately co-assemble with Kv2 subunits to form heterotetrameric channels which have distinct biophysical properties (Bocksteins and Snyders, 2012). The precise composition of KvS/Kv2 channels remains uncertain, with evidence for dominant Kv2:KvS stoichiometries of either 2:2 (Moller et al, 2020) or 3:1 (Kerschensteiner et al, 2005; Pisupati et al, 2018). Interestingly, KvS mRNAs are expressed in tissue and cell-specific manners that partially overlap with Kv2.1 and Kv2.2 expression (Castellano et al, 1997; Salinas et al, 1997b; Kramer et al, 1998; Bocksteins and Snyders, 2012; Bocksteins, 2016), suggesting that KvS subunits could generate diverse Kv2 channel subtypes, which modulate Kv2 function in a neuron-specific manner.…”
Section: Introductionmentioning
confidence: 99%
“…Another field of applications of our strategy are classic voltage-gated channels. In analogy, our strategy seems to be suitable to identifying the correct stoichiometry in heterotetrameric channels if part of the contributing subunits do not form functional channels on their own, as for example, Kv2.1/KV6.4 channels ( Moller et al, 2020 ; Pisupati et al, 2020 ). Here, a promising idea is to affect the voltage-sensor domain of the subunits by appropriate mutations, evoking shifts of steady-state activation to more positive voltages.…”
Section: Discussionmentioning
confidence: 99%